(untitled) (European Journal of Economics, Finance and Business Development, 2026)
The emergence and development of international financial centers (IFCs) represent one of the most significant phenomena in the global economic landscape. This article traces the theoretical evolution of the concept of international financial centers from the early twentieth-century notion of “world cities” to contemporary understandings of global financial hubs. The research examines the historical trajectory of major financial centers from medieval Italian city-states through contemporary global hubs, identifying critical factors that have determined their rise, dominance, and occasional decline. The findings reveal that successful IFCs are characterized by the concentration of international capital, liberal regulatory frameworks, advanced telecommunications infrastructure, and the presence of multinational corporations and financial institutions. The article concludes by synthesizing these theoretical and historical insights into a comprehensive definition of international financial centers and their role in the global economy.